PENGARUH HIDROLISIS ASAM-BASA TERHADAP AKTIVITAS PENANGKAPAN RADIKAL 2-2’ DIFENIL-1-PIKRIL HIDRAZIL (DPPH) FRAKSI AIR DARI EKSTRAK ETANOLIK BUAH TALOK (Muntingia calabura L.) - Tatang Irianti; Yosi Bayu Murti; Damiana Nitya Kanistri; Desi Riza Pratiwi; Kuswandi Kuswandi; Ratih Anggar Kusumaningtyas (Majalah Obat Tradisional, 2016)
The investigation of talok fruits (Muntingia calabura L.) was shown the antioxidant activity of aqueous fraction of the ethanolic extract is relatively low. Hydrolysis treatment has increased the antioxidant activity by releasing the flavonoid aglycone from glycoside form. This study aims to determine the effect of acid and alkaline hydrolysis, and hydrolysis time on the antioxidant activity of aqueous fraction of calabura fruits ethanolic extract. The antioxidant activity of acid hydrolyzed aqueous fractions in 1 and 3h hydrolysis, respectively 9.5 and 1.5 times more potent than the aqueous fraction, while the alkaline in 1 and 3h hydro-lysis were 2.5 and 6.5 times. Flavonoid aglycone liberated on acid hydrolysis and alkaline had different anti-oxidant activity. The value of IC50 by acid hydrolyzed aqueous fraction in 1h and 3h hydrolysis of 20.55 and 97.88μg/mL, while the alkaline in 1h and 3h hydrolysis of 66.64 and 25.53μg/mL. One hour acid hydrolysis had antioxidant activity greater than 3h whereas in alkaline the greatest antioxidant activity is shown in 3h.